Non-aqueous electrolyte secondary battery
By using acrylic resin in the negative electrode of the nonaqueous electrolyte secondary battery and containing LFSI lithium salt in the electrolyte solution, the problems of increasing contact resistance and decreasing cycle characteristics caused by expansion and contraction of Si-containing materials during charging and discharging are solved, and high capacity, low internal resistance and excellent cycle characteristics are achieved.
Patent Information
- Application Number
- CN201980014126.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-02-27
- Filing Date
- 2019-02-13
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2039-02-13
AI Technical Summary
The Si-containing material expands and contracts during the charging and discharging of the nonaqueous electrolyte secondary battery, resulting in an increase in the contact resistance between the negative electrode active material particles and the negative electrode current collector, and a decrease in the cycle characteristics.
Acrylic resin is used as a binder in the negative electrode, and lithium bis(fluorosulfonyl)imide (LFSI) lithium salt is contained in the electrolyte to inhibit swelling of the acrylic resin, maintain its high adhesion force, and reduce the increase of internal resistance and the reduction of cycle characteristics.
High capacity, low internal resistance and excellent cycle characteristics are achieved, ensuring efficient operation of the negative electrode active material and avoiding the problem of increasing the viscosity of the negative electrode slurry when increasing the bonding agent.
Smart Images

Figure CN111742436B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a nonaqueous electrolyte secondary battery. Background Art
[0002] In order to achieve high capacity of non-aqueous electrolyte secondary batteries, the use of Si-containing materials as negative electrode active materials has been studied. However, the expansion and contraction of Si-containing materials during charge and discharge is very large. Therefore, with repeated charge and discharge, the contact resistance between the negative electrode active material particles and between the negative electrode active material particles and the negative electrode collector increases. In addition, the coating (SEI: Solid Electrolyte Interface) on the surface of the negative electrode active material particles is destroyed, or the particles of the negative electrode active material are broken. As a result, the cycle characteristics are reduced.
[0003] As a method for suppressing the deterioration of the cycle characteristics, for example, there is a method of including polyacrylic acid in the negative electrode (Patent Document 1, etc.).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: International Publication No. 2016 / 121322 Summary of the invention
[0007] If an electrolyte is included in a negative electrode containing polyacrylic acid, the polyacrylic acid may swell. If the polyacrylic acid swells, the binding force of the polyacrylic acid between the negative electrode active material particles and between the negative electrode active material particles and the negative electrode collector is reduced. The Si-containing material has a large expansion and contraction during charge and discharge, so the internal resistance is likely to increase due to the reduction in binding force accompanying the expansion of the polyacrylic acid, and the cycle characteristics are also likely to decrease.
[0008] In view of the above, one aspect of the present invention relates to a non-aqueous electrolyte secondary battery, comprising: a positive electrode, a negative electrode and an electrolyte, wherein the negative electrode comprises: a negative electrode active material capable of electrochemically absorbing and releasing lithium, and a binder, the negative electrode active material comprises a Si-containing material, the binder comprises an acrylic resin, the electrolyte comprises a non-aqueous solvent, and a lithium salt dissolved in the non-aqueous solvent, and the lithium salt comprises lithium bis(fluorosulfonyl)imide: LFSI.
[0009] According to the present invention, a nonaqueous electrolyte secondary battery having high capacity, low internal resistance, and excellent cycle characteristics can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 This is a perspective schematic diagram in which a part of the nonaqueous electrolyte secondary battery according to one embodiment of the present invention is cut away. DETAILED DESCRIPTION
[0011] The non-aqueous electrolyte secondary battery of an embodiment of the present invention comprises: a positive electrode, a negative electrode and an electrolyte. The negative electrode comprises: a negative electrode active material capable of electrochemically absorbing and releasing lithium, and a binder. The negative electrode active material comprises a Si-containing material. The binder comprises an acrylic resin. The electrolyte comprises a non-aqueous solvent and a lithium salt (solute) dissolved in the non-aqueous solvent, and the lithium salt comprises lithium bis(fluorosulfonyl)imide: LiN(SO2F)2 (hereinafter also referred to as LFSI).
[0012] By making the negative electrode active material contain Si-containing materials, high capacity can be obtained, but the expansion and contraction of Si-containing materials during charge and discharge is large, so the internal resistance is easy to increase and the cycle characteristics are also easy to decrease. In contrast, by using acrylic resin as a binder and containing LFSI in the electrolyte, the increase in internal resistance and the decrease in cycle characteristics can be greatly suppressed. The reason is that when the negative electrode containing acrylic resin contains an electrolyte containing LFSI, the swelling of the acrylic resin is suppressed, the high binding force of the acrylic resin can be maintained, and the increase in contact resistance between the negative electrode active material particles and between the negative electrode active material particles and the negative electrode collector is suppressed.
[0013] In the case of suppressing the swelling of the acrylic resin, the reduction of the bonding force caused by the swelling of the acrylic resin is considered without increasing the amount of acrylic resin. Thus, even a small amount of acrylic resin (for example, 1.5 parts by mass or less per 100 parts by mass of the negative electrode active material) can ensure the bonding force. Thus, the amount of negative electrode active material contained in the negative electrode can be fully ensured, and high capacity can be achieved. In addition, the increase in the viscosity of the negative electrode slurry when the amount of acrylic resin is increased can also be avoided.
[0014] As factors that affect the degree of swelling of acrylic resin, for example, when an electrolyte is contained in a negative electrode containing acrylic resin, the ion concentration of the electrolyte and the ion concentration of the acrylic resin can be cited. For example, when the ion concentration of the electrolyte is lower than the ion concentration of the acrylic resin, if the ion concentration in the acrylic resin is to be reduced, the tendency of the solvent to penetrate from the outside to the inside of the acrylic resin increases, and the acrylic resin is prone to swelling. It can be considered that the large degree of dissociation of LFSI and the high Li ion concentration of the electrolyte are one of the factors that inhibit the swelling of the acrylic resin.
[0015] The acrylic resin is a polymer comprising at least one selected from the group consisting of (meth)acrylic acid units and (meth)acrylic acid salt units. The polymer may be a homopolymer or a copolymer. In the copolymer, the total amount of (meth)acrylic acid units and (meth)acrylic acid salt units is, for example, preferably 50 mol% or more, more preferably 80 mol% or more. It should be noted that in this specification, "(meth)acrylic acid unit" refers to at least one selected from the group consisting of "acrylic acid unit" and "methacrylic acid unit".
[0016] From the perspective of easy preparation of negative electrode slurry and improvement of battery characteristics, the acrylic resin preferably contains at least a unit of (meth)acrylate. In the above case, examples of (meth)acrylate include alkali metal salts such as lithium salts and sodium salts, ammonium salts, etc. Among them, from the perspective of reducing internal resistance, lithium salts of (meth)acrylate are preferred, and lithium salts of acrylic acid are more preferred.
[0017] From the viewpoint of facilitating preparation of negative electrode slurry and contributing to improvement of battery characteristics, the ratio (neutralization degree) of substitution of hydrogen atoms of carboxyl groups contained in the acrylic resin with alkali metal atoms is preferably 50% or more.
[0018] Specific examples of acrylic resins include polyacrylic acid, polymethacrylic acid, copolymers containing repeating units of acrylic acid and / or methacrylic acid (acrylic acid-methacrylic acid copolymers, ethylene-acrylic acid copolymers, etc.), or salts thereof, etc. These may be used alone or in combination of two or more.
[0019] The weight average molecular weight of the acrylic resin is preferably greater than or equal to 3000 and less than or equal to 10000000. When the weight average molecular weight of the acrylic resin is within the above range, the improvement effect of the cycle characteristics based on the acrylic resin and the reduction effect of the internal resistance can be fully obtained, and the gelation (viscosity increase) of the negative electrode slurry is suppressed, and the negative electrode is easily prepared.
[0020] The content of acrylic resin in the negative electrode is preferably 1.5 parts by mass or less per 100 parts by mass of the negative electrode active material. When the content of acrylic resin in the negative electrode is 1.5 parts by mass or less per 100 parts by mass of the negative electrode active material, the amount of the negative electrode active material can be fully ensured, and thus, further high capacity can be achieved. In the above case, the softness of the negative electrode can be fully ensured, and the cycle characteristics can be further improved. The viscosity of the negative electrode slurry can be reduced, and the negative electrode slurry can be easily prepared.
[0021] The content of acrylic resin in the negative electrode is more preferably 0.4 mass parts or more and 1.5 mass parts or less per 100 mass parts of the negative electrode active material. When the content of acrylic resin in the negative electrode is 0.4 mass parts or more per 100 mass parts of the negative electrode active material, the improvement effect of the cycle characteristics based on acrylic resin and the reduction effect of internal resistance can be fully obtained. The content of acrylic resin in the negative electrode is more preferably 0.5 mass parts or more and 1.5 mass parts or less per 100 mass parts of the negative electrode active material.
[0022] In the electrolyte, as a lithium salt dissolved in a non-aqueous solvent, LiPF6 may be included in addition to LFSI. LiPF6 easily forms a passivation film on the surface of components constituting the battery, such as an outer can. The passivation film has the function of protecting the above components. In this case, the ratio of LFSI to the total of LFSI and LiPF6 is preferably 7 mol% or more and 79 mol% or less, and more preferably 15 mol% or more and 50 mol% or less.
[0023] The lithium salt may contain other lithium salts in addition to LFSI and LiPF6, but the total amount of LFSI and LiPF6 in the lithium salt is preferably 80 mol% or more, more preferably 90 mol% or more. By controlling the total amount of LFSI and LiPF6 in the lithium salt to be within the above range, a battery with excellent cycle characteristics can be easily obtained.
[0024] The total concentration of LFSI and LiPF6 in the electrolyte is preferably 1 mol / L or more and 2 mol / L or less. Preferably, the concentration of LFSI in the electrolyte is 0.1 mol / L or more and 1.1 mol / L or less, and the concentration of LiPF6 in the electrolyte is 0.3 mol / L or more and 1.3 mol / L or less.
[0025] From the viewpoint of high capacity of the negative electrode, the negative electrode active material includes a Si-containing material (negative electrode material LSX described later, etc.) that electrochemically absorbs and releases lithium ions. However, the volume of the Si-containing material expands and shrinks with charging and discharging. Therefore, when the ratio of the Si-containing material in the negative electrode active material increases, poor contact between the negative electrode active material and the negative electrode collector is easily generated with charging and discharging. Therefore, the negative electrode active material preferably also includes a carbon material that electrochemically absorbs and releases lithium ions. By combining the Si-containing material with the carbon material, the high capacity of the Si-containing material can be given to the negative electrode and the cycle characteristics can be improved. From the viewpoint of high capacity and improved cycle characteristics, the ratio of the carbon material to the total of the Si-containing material and the carbon material is preferably less than 98% by mass, more preferably more than 70% by mass and less than 98% by mass, and further preferably more than 75% by mass and less than 95% by mass.
[0026] As the carbon material used in the negative electrode active material, for example, graphite, graphitizable carbon (soft carbon), non-graphitizable carbon (hard carbon), etc. can be exemplified. Among them, graphite with excellent charge-discharge stability and less irreversible capacity is preferred. Graphite refers to a material having a graphite-type crystal structure, for example, including natural graphite, artificial graphite, graphitized mesophase carbon particles, etc. The carbon material can be used alone or in combination of two or more kinds.
[0027] Next, the non-aqueous electrolyte secondary battery of the embodiment of the present invention will be described in detail. The non-aqueous electrolyte secondary battery includes, for example, the following negative electrode, positive electrode, and electrolyte.
[0028] [Negative Electrode]
[0029] The negative electrode includes, for example, a negative electrode current collector and a negative electrode mixture layer formed on the surface of the negative electrode current collector and containing a negative electrode active material. The negative electrode mixture layer can be formed as follows: by coating a negative electrode paste in which a negative electrode mixture is dispersed in a dispersion medium on the surface of the negative electrode current collector and drying, it can be formed. Calendering can be performed on the dried coating film as needed. The negative electrode mixture layer can be formed on one surface of the negative electrode current collector or on both surfaces.
[0030] The negative electrode mixture contains a negative electrode active material and a binder as essential components, and can contain a conductive agent, a thickener, etc. as optional components. The negative electrode active material contains at least the above-mentioned Si-containing material, and preferably also contains the above-mentioned carbon material.
[0031] As the Si-containing material, silicon oxide (SiO x : 0.5 ≤ x ≤ 1.5), a composite material containing a lithium silicate phase and silicon particles dispersed in the lithium silicate phase (hereinafter, also referred to as "negative electrode material LSX", or simply referred to as "LSX"), etc. can be cited. The higher the content of silicon particles in the negative electrode material LSX, the larger the negative electrode capacity becomes.
[0032] The lithium silicate phase preferably has a composition formula represented by Li y SiO z , satisfying 0 ≤ y ≤ 8 and 0.2 ≤ z ≤ 6. The composition formula is more preferably represented by Li 2u SiO 2+u (0 < u ≤ 2).
[0033] Compared with the composite of SiO2 and fine silicon, i.e., SiO x , the lithium silicate phase has fewer sites that can react with lithium, and it is not easy to generate an irreversible capacity accompanying charge and discharge. When the silicon particles are dispersed in the lithium silicate phase, excellent charge-discharge efficiency can be obtained at the initial stage of charge and discharge. In addition, since the content of the silicon particles can be arbitrarily changed, a high-capacity negative electrode can be designed.
[0034] The crystallite size of the silicon particles dispersed in the lithium silicate phase is, for example, greater than 10 nm. The silicon particles have a granular phase of a silicon (Si) single substance. When the crystallite size of the silicon particles is greater than 10 nm, the surface area of the silicon particles can be suppressed to be smaller, so it is not easy to cause degradation of the silicon particles accompanied by the generation of irreversible capacity. The crystallite size of the silicon particles is calculated from the half-value width of the diffraction peak attributable to the Si (111) plane of the X-ray diffraction (XRD) spectrum of the silicon particles according to the Scherrer formula.
[0035] The negative electrode material LSX also has excellent structural stability. The reason is that the silicon particles are dispersed in the lithium silicate phase, so the expansion and contraction of the negative electrode material LSX accompanying charging and discharging is suppressed. From the viewpoint of suppressing cracking of the silicon particles themselves, before the initial charge, the average particle size of the silicon particles is preferably 500nm or less, more preferably 200nm or less, and further preferably 50nm or less. After the initial charge, the average particle size of the silicon particles is preferably 400nm or less, more preferably 100nm or less. By miniaturizing the silicon particles, the volume change during charging and discharging is reduced, and the structural stability of the negative electrode material LSX is further improved.
[0036] The average particle size of silicon particles is measured by observing a cross-sectional SEM (scanning electron microscope) photograph of the negative electrode material LSX. Specifically, the average particle size of silicon particles is obtained by averaging the maximum particle sizes of any 100 silicon particles. Silicon particles are formed by agglomeration of a plurality of microcrystals.
[0037] From the viewpoint of high capacity, the content of silicon particles in the negative electrode material LSX can be, for example, 30% by mass or more, preferably 35% by mass or more. In the above case, the diffusibility of lithium ions is good, and excellent load characteristics are easily obtained. On the other hand, from the viewpoint of improving cycle characteristics, the content of silicon particles in the negative electrode material LSX is preferably 95% by mass or less, more preferably 75% by mass or less. The reason is that the surface of the silicon particles exposed without being covered with the lithium silicate phase is reduced, and the reaction between the electrolyte and the silicon particles is easily suppressed.
[0038] The content of silicon particles can be measured by Si-NMR. The following shows the ideal measurement conditions of Si-NMR.
[0039] Measuring device: Varian, solid-state nuclear magnetic resonance spectrometer (INOVA-400)
[0040] Probe: Varian 7mm CPMAS-2
[0041] MAS: 4.2kHz
[0042] MAS speed: 4kHz
[0043] Pulse: DD (45° pulse + signal collection time 1H decoupling)
[0044] Repeat time: 1200 seconds
[0045] Observation amplitude: 100kHz
[0046] Observation center: around -100ppm
[0047] Signal collection time: 0.05 seconds
[0048] Cumulative number of times: 560
[0049] Sample volume: 207.6 mg
[0050] Lithium silicate phase y SiO z The composition of can be analyzed, for example, by the following method.
[0051] First, the mass of the negative electrode material LSX sample is measured. Then, the contents of carbon, lithium, and oxygen contained in the sample are calculated as follows. Next, the carbon content is subtracted from the mass of the sample, the contents of lithium and oxygen in the remainder are calculated, and the ratio of y to z is obtained from the molar ratio of lithium (Li) to oxygen (O).
[0052] The carbon content is measured using a carbon / sulfur analyzer (e.g., EMIA-520 manufactured by Horiba, Ltd.). The sample is placed on a magnetic plate, a combustion aid is added, and the sample is inserted into a combustion furnace heated to 1350°C (carrier gas: oxygen). The amount of carbon dioxide gas generated during combustion is detected by infrared absorption. A standard curve is prepared, for example, using carbon steel (carbon content 0.49%) manufactured by Bureau of Analyzed Samples. Ltd., and the carbon content of the sample is calculated (high-frequency induction heating furnace combustion-infrared absorption method).
[0053] The oxygen content is measured using an oxygen / nitrogen / hydrogen analyzer (e.g., EGMA-830 manufactured by Horiba, Ltd.). The sample is placed in a Ni capsule and placed in a carbon crucible heated with 5.75 kW of electricity together with Sn pellets and Ni pellets that become flux, and the released carbon monoxide gas is detected. A standard curve is prepared using a standard sample Y2O3, and the oxygen content of the sample is calculated (inert gas melting-non-dispersive infrared absorption method).
[0054] The lithium content is determined by completely dissolving the sample in hot fluorinated nitric acid (a mixture of heated hydrofluoric acid and nitric acid), filtering and removing the dissolved residual carbon, and analyzing the resulting filtrate by inductively coupled plasma atomic emission spectrometry (ICP-AES). A standard curve is prepared using a commercially available lithium standard solution to calculate the lithium content of the sample.
[0055] The amount obtained by subtracting the carbon content, oxygen content, and lithium content from the mass of the sample of the negative electrode material LSX is the silicon content. The silicon content includes contributions from both silicon in the form of silicon particles and silicon in the form of lithium silicate. The content of silicon particles is determined by Si-NMR measurement, and the content of silicon in the form of lithium silicate in the negative electrode material LSX is determined.
[0056] The negative electrode material LSX is preferably formed into a granular material (hereinafter also referred to as LSX particles) with an average particle size of 1 to 25 μm, and further 4 to 15 μm. When it is in the above particle size range, it is easy to relax the stress caused by the volume change of the negative electrode material LSX accompanying charge and discharge, and it is easy to obtain good cycle characteristics. The surface area of the LSX particles also becomes moderate, and the capacity reduction caused by the side reaction with the non-aqueous electrolyte is also suppressed.
[0057] The average particle size of LSX particles refers to the particle size (volume average particle size) at which the volume cumulative value is 50% in the particle size distribution measured by the laser diffraction scattering method. For example, the measuring device "LA-750" manufactured by HORIBA Ltd. can be used.
[0058] The LSX particles preferably have a conductive material covering at least a portion of their surface. The lithium silicate phase lacks electronic conductivity, so the conductivity of the LSX particles is also likely to be low. By covering the surface with a conductive material, the conductivity can be greatly improved. The conductive layer is preferably thin enough not to substantially affect the average particle size of the LSX particles.
[0059] As the negative electrode current collector, a non-porous conductive substrate (metal foil, etc.) or a porous conductive substrate (net, mesh, punched sheet, etc.) can be used. As the material of the negative electrode current collector, stainless steel, nickel, nickel alloy, copper, copper alloy, etc. can be exemplified. The thickness of the negative electrode current collector is not particularly limited, but from the viewpoint of the balance between the strength and lightness of the negative electrode, 1 to 50 μm is preferred, and 5 to 20 μm is more desirable.
[0060] The binder contains at least the above-mentioned acrylic resin. As the binder, in addition to the above-mentioned acrylic resin, fluororesins such as polytetrafluoroethylene and polyvinylidene fluoride; polyolefin resins such as polyethylene and polypropylene; polyamide resins such as aramid resins; polyimide resins such as polyimide and polyamideimide; vinyl resins such as polyacrylonitrile and polyvinyl acetate; polyvinyl pyrrolidone; polyether sulfone; rubber-like materials such as styrene-butadiene copolymer rubber (SBR), etc. can be used. They can be used alone or in combination of two or more.
[0061] As the conductive agent, for example, carbon materials such as acetylene black and carbon nanotubes; conductive fibers such as carbon fibers and metal fibers; carbon fluoride; metal powders such as aluminum; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; organic conductive materials such as phenylene derivatives, etc. These materials may be used alone or in combination of two or more.
[0062] Examples of thickeners include carboxymethyl cellulose (CMC) and modified products thereof (including salts such as Na salts), cellulose derivatives such as methyl cellulose (cellulose ethers, etc.), saponified polymers having vinyl acetate units such as polyvinyl alcohol, polyethers (polyalkylene oxides such as polyethylene oxide), etc. These may be used alone or in combination of two or more.
[0063] The dispersion medium is not particularly limited, and examples thereof include water, alcohols such as ethanol, ethers such as tetrahydrofuran, amides such as dimethylformamide, N-methyl-2-pyrrolidone (NMP), and mixed solvents thereof.
[0064] [positive electrode]
[0065] The positive electrode, for example, comprises: a positive electrode current collector, and a positive electrode mixture layer formed on the surface of the positive electrode current collector. The positive electrode mixture layer can be formed as follows: a positive electrode slurry in which a positive electrode mixture is dispersed in a dispersion medium is applied to the surface of the positive electrode current collector, and the mixture is dried to form the positive electrode current collector. The dried coating film can be rolled as needed. The positive electrode mixture layer can be formed on one surface of the positive electrode current collector or on both surfaces.
[0066] As the positive electrode active material, a lithium composite metal oxide can be used. For example, Li a CoO2、Li a NiO2、Li a MnO2、Li a Co b Ni 1-b O2、Li a Co b M 1-b O c , Li a Ni 1-b M b O c , Li a Mn2O4、Li a Mn 2-b M bO4, LiMPO4, Li2MPO4F (M is at least one of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, B). Here, a = 0 to 1.2, b = 0 to 0.9, c = 2.0 to 2.3. It should be noted that the value of a representing the molar ratio of lithium is the value just after the active material is produced, and it increases or decreases according to charge and discharge.
[0067] Among them, Li is preferred a Ni b M 1-b lithium nickel composite oxide represented by O2 (M is at least one selected from the group consisting of Mn, Co, and Al, 0 < a ≤ 1.2, 0.3 ≤ b ≤ 1). From the viewpoint of high capacity, it is more preferably that 0.85 ≤ b ≤ 1. Further, from the viewpoint of the stability of the crystal structure, it is further preferably Li containing Co and Al as M a Ni b Co c Al d O2 (0 < a ≤ 1.2, 0.85 ≤ b < 1, 0 < c < 0.15, 0 < d ≤ 0.1, b + c + d = 1).
[0068] As the binder and the conductive agent, the same substances as those exemplified for the negative electrode can be used. As the conductive agent, graphite such as natural graphite and artificial graphite can be used.
[0069] The shape and thickness of the positive electrode current collector can be selected based on the shape and range conforming to the negative electrode current collector. As the material of the positive electrode current collector, for example, stainless steel, aluminum, aluminum alloy, titanium, etc. can be exemplified.
[0070] [Electrolyte]
[0071] The electrolyte contains a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent, and the lithium salt contains LFSI.
[0072] The concentration of the lithium salt in the electrolyte is preferably, for example, 0.5 mol / L or more and 2 mol / L or less. By controlling the lithium salt concentration within the above range, an electrolyte with excellent ionic conductivity and moderate viscosity can be obtained. However, the lithium salt concentration is not limited to the above.
[0073] As the lithium salt other than LFSI, known lithium salts can be used. As preferred lithium salts, for example, the following can be cited: LiClO4, LiBF4, LiPF6, LiAlCl4, LiSbF6, LiSCN, LiCF3SO3, LiCF3CO2, LiAsF6, LiB 10 Cl 10, lower aliphatic carboxylic acid lithium, LiCl, LiBr, LiI, borates, imide salts, etc. As borates, there can be mentioned lithium bis(1,2-benzenedioleate (2-)-O,O')borate, lithium bis(2,3-naphthalenedioleate (2-)-O,O')borate, lithium bis(2,2'-biphenyledioleate (2-)-O,O')borate, lithium bis(5-fluoro-2-oleate-1-benzenesulfonic acid-O,O')borate, etc. As imide salts, there can be mentioned lithium bis(trifluoromethanesulfonic acid imide) (LiN(CF3SO2)2), lithium trifluoromethanesulfonic acid nonafluorobutanesulfonic acid imide (LiN(CF3SO2)(C4F9SO2)), lithium bis(pentafluoroethanesulfonic acid imide) (LiN(C2F5SO2)2), etc. Among them, LiPF6 is more preferred. The lithium salt may be used alone or in combination of two or more.
[0074] As the non-aqueous solvent, for example, cyclic carbonates (excluding unsaturated cyclic carbonates described later), chain carbonates, cyclic carboxylates, chain carboxylates, etc. can be used. As cyclic carbonates, propylene carbonate (PC), ethylene carbonate (EC), etc. can be mentioned. As chain carbonates, diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), etc. can be mentioned. As cyclic carboxylates, γ-butyrolactone (GBL), γ-valerolactone (GVL), etc. can be mentioned. As chain carboxylates, methyl formate, ethyl formate, propyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, etc. can be mentioned. The non-aqueous solvent can be used alone or in combination of two or more.
[0075] The non-aqueous solvent preferably contains a chain carboxylate. In the above case, the lithium salt (LFSI, etc.) in the electrolyte is easily dissociated, which is beneficial to suppress the swelling of the acrylic resin. The ratio of the chain carboxylate in the non-aqueous solvent is preferably 4 volume % or more and 90 volume % or less.
[0076] In the electrolyte, a cyclic carbonate (hereinafter referred to as unsaturated cyclic carbonate) having at least one carbon-carbon unsaturated bond in the molecule may also be included as an additive. The unsaturated cyclic carbonate decomposes on the negative electrode to form a high lithium ion conductivity film on the negative electrode surface, which can improve the charge and discharge efficiency.
[0077] As unsaturated cyclic carbonate, known compounds can be used. As preferred unsaturated cyclic carbonate, for example, vinylene carbonate, 4-methyl vinylene carbonate, 4,5-dimethyl vinylene carbonate, 4-ethyl vinylene carbonate, 4,5-diethyl vinylene carbonate, 4-propyl vinylene carbonate, 4,5-dipropyl vinylene carbonate, 4-phenyl vinylene carbonate, 4,5-diphenyl vinylene carbonate, vinyl ethylene carbonate, divinyl ethylene carbonate, etc. can be enumerated. Wherein, preferably at least one selected from the group consisting of vinylene carbonate, vinyl ethylene carbonate and divinyl ethylene carbonate. Unsaturated cyclic carbonate can be used alone or in combination of two or more. A part of hydrogen atoms of unsaturated cyclic carbonate can be substituted by fluorine atoms.
[0078] [Separator]
[0079] It is usually desirable to sandwich a separator between the positive electrode and the negative electrode. The separator has high ion permeability and has appropriate mechanical strength and insulation. As the separator, a microporous film, woven fabric, non-woven fabric, etc. can be used. As the material of the separator, polyolefins such as polypropylene and polyethylene are preferred.
[0080] As an example of the structure of a non-aqueous electrolyte secondary battery, the following structure can be cited: an electrode group formed by winding a positive electrode and a negative electrode with a separator, and a non-aqueous electrolyte are contained in an outer shell. Alternatively, an electrode group of other forms such as a stacked electrode group formed by stacking a positive electrode and a negative electrode with a separator can also be used instead of a wound electrode group. The non-aqueous electrolyte secondary battery can be, for example, in any form such as a cylindrical type, a square type, a coin type, a button type, a laminated type, etc.
[0081] Figure 1 This is a perspective schematic diagram in which a portion of a rectangular nonaqueous electrolyte secondary battery according to one embodiment of the present invention is cut away.
[0082] The battery comprises: a battery case 6 having a bottom and a square shape, an electrode group 9 and an electrolyte (not shown) housed in the battery case 6. The electrode group 9 comprises: a long strip-shaped negative electrode, a long strip-shaped positive electrode, and a separator sandwiched therebetween to prevent direct contact. The electrode group 9 can be formed by winding the negative electrode, the positive electrode and the separator around a flat winding core and removing the winding core.
[0083] One end of the negative electrode lead 14 is attached to the negative electrode collector of the negative electrode by welding or the like. One end of the positive electrode lead 11 is attached to the positive electrode collector of the positive electrode by welding or the like. The other end of the negative electrode lead 14 is electrically connected to the negative electrode terminal 13 provided on the sealing plate 5. The other end of the positive electrode lead 11 is electrically connected to the battery case 6 which also serves as the positive terminal. A resin frame 4 is arranged on the upper part of the electrode group 9, which separates the electrode group 9 from the sealing plate 5 and separates the negative electrode lead 14 from the battery case 6. In addition, the opening of the battery case 6 is sealed by the sealing plate 5.
[0084] Hereinafter, the present invention will be specifically described based on Examples and Comparative Examples, but the present invention is not limited to the following Examples.
[0085] <Example 1>
[0086] [Preparation of negative electrode material LSX]
[0087] Silicon dioxide and lithium carbonate were mixed so that the atomic ratio Si / Li was 1.05, and the mixture was calcined in air at 950°C for 10 hours to obtain lithium silicate represented by the formula: Li2Si2O5 (u=0.5). The obtained lithium silicate was pulverized to an average particle size of 10 μm.
[0088] Lithium silicate (Li2Si2O5) with an average particle size of 10 μm and raw silicon (3N, average particle size of 10 μm) were mixed at a mass ratio of 45:55. The mixture was filled into a planetary ball mill (manufactured by Fritsch, P-5) pot (SUS, volume: 500 mL), 24 SUS balls (diameter 20 mm) were placed in the pot, and the pot was covered with a lid, and the mixture was pulverized at 200 rpm in an inert atmosphere for 50 hours.
[0089] Next, the powdered mixture was taken out in an inert atmosphere, and calcined at 800° C. for 4 hours in the inert atmosphere under pressure using a hot press, thereby obtaining a sintered body of the mixture (negative electrode material LSX).
[0090] After that, the negative electrode material LSX was crushed and passed through a 40 μm sieve, and the obtained LSX particles were mixed with coal tar (MCP250 manufactured by JFEChemical Corporation), and the mixture was baked at 800°C in an inert atmosphere to cover the surface of the LSX particles with conductive carbon to form a conductive layer. The covering amount of the conductive layer was set to 5% by mass relative to the total mass of the LSX particles and the conductive layer. After that, LSX particles with an average particle size of 5 μm having a conductive layer were obtained by sieving.
[0091] The crystallite size of the silicon particles calculated by the Scherrer equation from the diffraction peak attributed to the Si (111) plane through XRD analysis of the LSX particles was 15 nm.
[0092] The composition of the lithium silicate phase was analyzed by the above-mentioned methods (high-frequency induction heating furnace combustion-infrared absorption method, inert gas melting-non-dispersive infrared absorption method, inductively coupled plasma emission spectrometry (ICP-AES)). The results showed that the Si / Li ratio was 1.0, and the Li2Si2O5 content measured by Si-NMR was 45 mass% (the content of silicon particles was 55 mass%).
[0093] [Production of negative electrode]
[0094] The LSX particles with a conductive layer were mixed with graphite and used as a negative electrode active material. The ratio of graphite to the total of the LSX particles with a conductive layer and graphite was set to 94% by mass. The negative electrode active material was mixed with lithium salt of polyacrylic acid (PAA-Li), sodium carboxymethyl cellulose (CMC-Na) and styrene-butadiene rubber (SBR), and after adding water, it was stirred with a mixer (manufactured by Primix, TKHIVIS MIX) to prepare a negative electrode slurry.
[0095] PAA-Li used was a material with a neutralization degree of 95% and a weight average molecular weight of 100,000. The amount of PAA-Li added was 1 part by mass per 100 parts by mass of the negative electrode active material. The amount of CMC-Na added was 1 part by mass per 100 parts by mass of the negative electrode active material. The amount of SBR added was 1 part by mass per 100 parts by mass of the negative electrode active material.
[0096] Next, the negative electrode slurry was applied on the surface of the copper foil so that every 1 m 2 The mass of the negative electrode mixture was 190 g, and the coating was dried and rolled to form a copper foil with a density of 1.5 g / cm 3 The negative electrode of the negative electrode mixture layer.
[0097] [Production of positive electrode]
[0098] The lithium nickel composite oxide (LiNi 0.8 Co 0.18 Al 0.02 O2) and acetylene black and polyvinylidene fluoride, add N-methyl-2-pyrrolidone (NMP), stir with a mixer (Primix, TKHIVIS MIX) to prepare positive electrode slurry. Then, the positive electrode slurry is applied to the surface of the aluminum foil, and the coating is dried and rolled to form a 3.6 g / cm2 film on both sides of the aluminum foil. 3 The positive electrode of the positive electrode mixture layer.
[0099] [Preparation of electrolyte]
[0100] The electrolyte is prepared by dissolving a lithium salt in a non-aqueous solvent. The non-aqueous solvent used is a mixed solvent containing ethylene carbonate (EC), dimethyl carbonate (DMC) and methyl acetate (MA) in a volume ratio of 20:40:40. The lithium salts used are LFSI and LiPF6. The concentrations of LFSI and LiPF6 in the electrolyte are set to the values shown in Table 1, respectively.
[0101] [Fabrication of non-aqueous electrolyte secondary battery]
[0102] The sheet was mounted on each electrode, and the positive electrode and the negative electrode were wound into a spiral shape with the separator sandwiched so that the sheet was located at the outermost periphery, thereby preparing an electrode group. The electrode group was inserted into an outer casing made of an aluminum laminate film, vacuum dried at 105° C. for 2 hours, and then a nonaqueous electrolyte was injected and the opening of the outer casing was sealed to obtain a battery A1.
[0103] <Examples 2 to 9>
[0104] In the preparation of the negative electrode, the ratio of graphite to the total of the LSX particles having a conductive layer and graphite was set to the value shown in Table 1, and the amount of PAA-Li added per 100 parts by mass of the negative electrode active material was set to the value shown in Table 1. In the preparation of the electrolyte, the concentration of LFSI in the electrolyte and the concentration of LiPF6 in the electrolyte were set to the values shown in Table 1. Batteries A2 to A9 were prepared in the same manner as in Example 1 except for the above.
[0105] <Comparative Example 1>
[0106] In the preparation of the negative electrode, the ratio of graphite to the total of the LSX particles having a conductive layer and graphite was set to 91% by mass, and PAA-Li was not used. In the preparation of the electrolyte, only LiPF6 was used as the lithium salt, and the concentration of LiPF6 in the electrolyte was set to 1.2 mol / L. Battery B1 was prepared in the same manner as in Example 1 except for the above.
[0107] <Comparative Example 2>
[0108] In the preparation of the electrolyte solution, only LiPF6 was used as the lithium salt and the concentration of LiPF6 in the electrolyte solution was adjusted to 1.2 mol / L. Battery B2 was produced in the same manner as in Example 1.
[0109] <Comparative Example 3>
[0110] Battery B3 was produced in the same manner as in Example 1 except that PAA-Li was not used in the production of the negative electrode.
[0111] <Comparative Example 4>
[0112] In the preparation of the negative electrode, only graphite was used as the negative electrode active material, and the amount of PAA-Li added was 0.5 parts by mass per 100 parts by mass of the negative electrode active material. In the preparation of the electrolyte, only LiPF6 was used as the lithium salt, and the concentration of LiPF6 in the electrolyte was 1.0 mol / L. Battery B4 was prepared in the same manner as Example 1 except for the above.
[0113] Each of the batteries produced above was evaluated by the following methods.
[0114] [Evaluation 1: Initial capacity]
[0115] The battery was charged at a constant current of 0.3 It (990 mA) until the voltage reached 4.2 V, and then charged at a constant voltage of 4.2 V until the current reached 0.015 It (50 mA). After that, the battery was discharged at a constant current of 0.3 It (990 mA) until the voltage reached 2.75 V. The pause time between charging and discharging was set to 10 minutes. Charging and discharging were performed at 25 ° C. The discharge capacity D1 at this time was calculated as the initial capacity.
[0116] [Evaluation 2: Internal resistance (DC-IR)]
[0117] The battery was charged and discharged under the same conditions as in the above evaluation 1, and then charged under the same conditions as in the above evaluation 1. After charging, the battery was paused for 60 minutes, and a constant current discharge was performed for 10 seconds at a current of 0.3 It (990 mA). The difference between the voltage before the start of discharge and the voltage 10 seconds after the start of self-discharge was divided by the current value of 0.3 It to obtain the value as the initial internal resistance (DC-IR).
[0118] [Evaluation 3: Cycle capacity maintenance rate]
[0119] The battery was charged at a constant current of 0.3 It (990 mA) until the voltage reached 4.2 V, and then charged at a constant voltage of 4.2 V until the current reached 0.015 It (50 mA). After that, the battery was discharged at a constant current of 0.3 It (990 mA) until the voltage reached 2.75 V. The pause time between charging and discharging was set to 10 minutes. Charging and discharging were performed at 25 ° C.
[0120] The charge and discharge were repeated under the above-mentioned charge and discharge conditions, and the ratio of the discharge capacity at the 500th cycle to the discharge capacity at the 1st cycle was determined as the cycle capacity retention rate.
[0121] The evaluation results are shown in Table 1. It should be noted that the amount of PAA-Li in Table 1 is the amount (parts by mass) relative to 100 parts by mass of the negative electrode active material. The amount of graphite is the ratio (mass %) of graphite in the total of the LSX particles (Si-containing material) having a conductive layer and graphite. C1+C2 is the total concentration (mol / L) of LFSI and LiPF6 in the electrolyte. C1 / (C1+C2)×100 is the ratio (mol %) of LFSI in the total of LFSI and LiPF6.
[0122] [Table 1]
[0123]
[0124] Batteries A1 to A9 of Examples 1 to 9 showed high initial capacity, low internal resistance, and high cycle capacity retention rate.
[0125] In particular, in batteries A1 to A5 of Examples 1 to 5, higher initial capacity, lower internal resistance and higher cycle capacity maintenance rate were obtained. In Examples 1 to 5, the amount of graphite was 98% by mass or less, and the amount of PAA-Li was 1.5 parts by mass or less. The total concentration of LFSI and LiPF6 in the electrolyte was 1 mol / L or more and 2 mol / L or less, and the ratio of LFSI to the total of LFSI and LiPF6 was 7 mol% or more and 79 mol% or less. The concentration of LFSI in the electrolyte was 0.1 mol / L or more and 1.1 mol / L or less, and the concentration of LiPF6 in the electrolyte was 0.3 mol / L or more and 1.3 mol / L or less.
[0126] In the battery B1 of Comparative Example 1, PAA-Li and LFSI are not used, so the internal resistance increases, the initial capacity decreases, and the cycle capacity retention rate decreases. In the battery B2 of Comparative Example 2, LFSI is not used, so the internal resistance increases, the initial capacity decreases, and the cycle capacity retention rate decreases. In the battery B3 of Comparative Example 3, PAA-Li is not used, so the internal resistance increases, the initial capacity decreases, and the cycle capacity retention rate decreases. In the battery B4 of Comparative Example 4, LFSI is not used, so the internal resistance increases, the cycle capacity retention rate decreases, and LFSI and Si-containing materials are not used, so the initial capacity decreases.
[0127] Industrial Applicability
[0128] The nonaqueous electrolyte secondary battery of the present invention is useful as a main power source for mobile communication equipment, portable electronic equipment, and the like.
[0129] Description of Reference Numerals
[0130] 4 Frame
[0131] 5 Sealing plate
[0132] 6 Battery housing
[0133] 9 Electrode Group
[0134] 11 Positive lead
[0135] 13 Negative terminal
[0136] 14 Negative lead
Claims
1. A non-aqueous electrolyte secondary battery comprising: a positive electrode, a negative electrode and an electrolyte solution, The negative electrode comprises: a negative electrode active material capable of electrochemically storing and releasing lithium, and a binder. The negative electrode active material comprises a carbon material and a Si-containing material, The binder comprises an acrylic resin, The electrolyte solution comprises a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent. The lithium salt comprises lithium bis(fluorosulfonyl)imide: LFSI and LiPF6, wherein the ratio of LFSI to the total of LFSI and LiPF6 is 7 mol% or more and 19 mol% or less, The ratio of the carbon material to the total of the Si-containing material and the carbon material is 90 mass % or more and 98 mass % or less.
2. The nonaqueous electrolyte secondary battery according to claim 1, wherein The Si-containing material comprises a composite material comprising a lithium silicate phase and silicon particles dispersed in the lithium silicate phase, The crystallite size of the silicon particles is greater than 10 nm.
3. The nonaqueous electrolyte secondary battery according to claim 2, wherein: The composition formula of the lithium silicate phase is Li 2u SiO 2+u , where 0 <u≤2。 4. The nonaqueous electrolyte secondary battery according to any one of claims 1 to 3, wherein The acrylic resin contains at least a (meth)acrylate unit.
5. The nonaqueous electrolyte secondary battery according to claim 4, wherein The (meth)acrylate salt is a lithium salt of (meth)acrylic acid.
6. The nonaqueous electrolyte secondary battery according to any one of claims 1 to 3, wherein A content of the acrylic resin in the negative electrode is 1.5 parts by mass or less per 100 parts by mass of the negative electrode active material.
7. The nonaqueous electrolyte secondary battery according to claim 1, wherein The total concentration of the LFSI and the LiPF6 in the electrolyte is 1 mol / L or more and 2 mol / L or less.
8. The nonaqueous electrolyte secondary battery according to claim 1, wherein The concentration of the LFSI in the electrolyte is 0.1 mol / L or more and 1.1 mol / L or less, The concentration of the LiPF6 in the electrolyte is greater than or equal to 0.3 mol / L and less than or equal to 1.3 mol / L.
9. The nonaqueous electrolyte secondary battery according to any one of claims 1 to 3, wherein The nonaqueous solvent includes a chain carboxylic acid ester.
Citation Information
Patent Citations
Negative electrode plate for nonaqueous electrolyte secondary batteries and nonaqueous electrolyte secondary battery using said negative electrode plate
WO2016121322A1
Negative electrode active material for non-aqueous electrolyte secondary batteries, and non-aqueous electrolyte secondary battery
CN107112522A
Nonaqueous electrolyte secondary battery
CN107251304A
Nonaqueous electrolyte secondary battery
JP2006210208A
Nonaqueous electrolyte secondary battery
JP2014067583A